IMPROVING STUDENTS’ VOCABULARY BY USING RIDDLE GAME A Classroom Action Research on the Seventh Grade Students of SMP Negeri 8 Pontianak in Academic Year 2014/2015 - Sabriana, Ria; Supardi, Iwan; Novita, Dewi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The aim of this research is to improve students’ vocabulary, especially in meaning and spelling of vocabularies. This research was conducted on the seventh grade students of SMP Negeri 8 Pontianak in academic year 2014/2015. In this research, the subject is class VII E that consists of 30 students. The researcher conducted a classroom action research in her research and acted as the teacher during the research period. The data were collected by using direct and measurement technique. The tools of data collecting were observation checklist, field note, and test. Riddle game was used as the technique in this research which is conducted the research in two cycles. The research findings showed that the mean score of students’ vocabulary test in the first cycle is 59.83 to 76.20 in the second cycle which means it successffully passed the KKM. It can be concluded that the students’ vocabulary taught by using riddle game was improved. Keywords: Vocabulary, Game, Riddle Game Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan siswa dalam kosakata. Penelitian ini telah dilakukan terhadap siswa kelas VII SMP N 8 Pontianak pada tahun akademik 2014/2015. Dalam penelitian ini sasaran penelitiannya adalah siswa kelas VII E yang terdiri dari 30 orang siswa. Penelitian ini menggunakan metode penelitian tindakan kelas dan berperan sebagai guru selama masa penelitia berlangsung. Data dikumpulkan menggunakan tehnik penilaian dan observasi langsung dengan menggunakan tabel pemeriksaan, catatan lapangan, dan tes. Tehnik yang digunakan adalah riddle game dan dilaksanakan dalam 2 siklus. Hasil penelitian menunjukan skor rata-rata tes siswa pada siklus pertama adalah 59,83 menjadi 76,20 pada siklus kedua yang berarti siswa dapat melewati standar KKM. Berdasarkan hasil tersebut, dapat disimpulkan bahwa pemahaman siswa terhadap kosakata, khususnya pada arti dan pengejaan kata dapat meningkat melalui pengajaran menggunakan riddle game. Keywords: Kosakata, Permainan, Riddle Game